PENGARUH PENAMBAHAN SERBUK DAUN STEVIA DAN PEKTIN DAUN CINCAU HIJAU TERHADAP SIFAT FISIK, KIMIA, DAN ORGANOLEPTIK SELAI BUAH NAGA MERAH - Verta Hedyana; Mochammad Wachid; Noor Harini (Universitas Muhammadiyah Malang, 2021)
Dragon fruit can be processed into a jam with sugar, pectin, and acid addition. Pectin can be extracted from natural ingredient such as green grass jelly leaf. Stevia leaf powder can be added to a jam as natural sweetener. This study used factorial randomized block design with 3 levels concentration of pectin (0.75%, 1%, 1.25%) and 3 levels concentration of stevia powder (0.5%, 0.75%, 1%). The analyzed parameter such as water content, pH, spreadability, color intensity, total dissolved solid, and organoleptics. Based on the result, there was an interaction between the pectin concentration of green grass jelly leaves and the concentration of stevia leaves on texture and colour of dragon fruit jam.